Effective Passivation of C-Si by Intrinsic A-Si:h Layer for hit Solar Cells - Shahaji More; R.O. Dusane (Журнал нано- та електронної фізики)
The influence of HF solution etching on surface roughness of c-Si wafer was investigated using AFM. Ultra thin(2-3 nm) intrinsic a-Si:H is necessary to achieve high VOC and Fill factor, as it effectively passivates the defects on the surface of c-Si and increase tunneling probability of minority charge carriers. However, to achieve control over ultra-thin intrinsic a-Si:H layer thickness and passivation properties, the films were deposited by Hot-wire CVD. We used tantalum filament and silane (SiH4) as a precursor gas, where as the deposition parameter such as filament temperature temperature was varied. The deposition rate, Dark and Photoconductivity were measured for all the films. The optimized intrinsic a-Si:H layer was inserted between p typed doped layers and n type c-Si wafers to fabricate HIT solar cells. The Current-Voltage characteristics were studied to understand the passivation effect of intrinsic layer on c-Si surface. The high saturation current density (Jsat > 10–7 A/cm2) and Ideality factor (n > 2) were observed. We achieved the efficiency of 3.28 % with the optimized intrinsic and doped a-Si:H layers using HWCVD technique.